2018
DOI: 10.1111/ina.12445
|View full text |Cite|
|
Sign up to set email alerts
|

Routes of transmission of influenza A H1N1, SARS CoV, and norovirus in air cabin: Comparative analyses

Abstract: Identifying the exact transmission route(s) of infectious diseases in indoor environments is a crucial step in developing effective intervention strategies. In this study, we proposed a comparative analysis approach and built a model to simulate outbreaks of 3 different in-flight infections in a similar cabin environment, that is, influenza A H1N1, severe acute respiratory syndrome (SARS) coronavirus (CoV), and norovirus. The simulation results seemed to suggest that the close contact route was probably the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 37 publications
2
136
0
Order By: Relevance
“…For rhinovirus and norovirus, none of the interventions considered had an appreciable effect, suggesting that alternative strategies may be needed to control these pathogens. These results are consistent with recent work by Lei et al, who found that the fomite-mediated route was important for norovirus, but less so for influenza [28]. To be effective, surface decontamination interventions for norovirus and rhinovirus may need to be more frequent (> 1x /day), tailored to the specific context, and timed early in outbreaks to interrupt transmission.…”
Section: Characterizing Pathogenssupporting
confidence: 90%
“…For rhinovirus and norovirus, none of the interventions considered had an appreciable effect, suggesting that alternative strategies may be needed to control these pathogens. These results are consistent with recent work by Lei et al, who found that the fomite-mediated route was important for norovirus, but less so for influenza [28]. To be effective, surface decontamination interventions for norovirus and rhinovirus may need to be more frequent (> 1x /day), tailored to the specific context, and timed early in outbreaks to interrupt transmission.…”
Section: Characterizing Pathogenssupporting
confidence: 90%
“…Similar results have been obtained for SARS and MERS in other studies as well [122]. For example, Lei et al (2018) modeled in-flight outbreaks of influenza A H1N1, SARS, and norovirus in an air cabin, and predicted that the dominant route of transmission was a close contact for influenza and contact with fomites for SARS and norovirus [123]. Many others have also developed and applied models for investigating the transmission dynamics of generic [124] and specific pathogens, including influenza [125][126][127][128], norovirus [129], rotavirus [130], and cholera [127].…”
Section: Mechanistic Modelssupporting
confidence: 89%
“…SARS-CoV-2 is a single-stranded RNA virus that can be transmitted from human to human; comparable to the transmission of SARS and MERS, SARS-CoV-2 is also transmitted primarily through respiratory droplets and contact [6,7]. In this study, we had marginally more female subjects than male subjects, which could be related to the fact that the average age of men was lower than that of women.…”
Section: Discussionmentioning
confidence: 82%